Fabrication and Assessment of Bifunctional Electrospun Poly(L-Lactic Acid) Scaffolds with Bioglass and Zinc Oxide Nanoparticles for Bone Tissue Engineering - Zapata-Ramirez, P; Canales-Arévalo, D; Loyo-Davila, C; Saavedra-Gonzalez, M (Elsevier B.V., 2023)
Electrospun scaffolds based on poly(L-lactic acid) (PLLA) with bioglass (n-BG) and zinc oxide (n-ZnO), and mixture of both, were developed to design bifunctional biomaterials with enhanced bioactive and biocidal properties. The presence of n-BG increased the fiber diameter of the pure PLA from 1.5 ± 0.3 μm to 3.0 ± 0.8 μm for 20 wt%. ZnO and the mixed nanoparticles did not significantly affect the morphology. The mechanical properties decreased with the presence of nanoparticles. Scaffolds based on PLA/n-BG promoted hydroxyapatite (HA) formation in simulated body fluid (SBF) that was inhibited with the presence of ZnO. Notably, mixed particles produced bioactivity although at longer times. The incorporation of n-ZnO produced a biocidal capacity against S. aureus in the polymeric scaffold, reaching a viability reduction of 60 % after 6 h of exposure. When both types of nanoparticles were combined, the bacterial viability reduction was 30 %. Pure PLA scaffolds and the composites with n-BG showed good ST-2 bone marrow-derived cell line viability, scaffolds with n-BG (pure or mixture) presented lower viability. Results validated the use of both n-BG and n-ZnO fillers for the development of novel bifunctional PLA-based scaffolds with both bioactive and biocidal properties for bone tissue engineering applications. © 2022 Elsevier B.V.
Keywords: Bone tissue engineering; Electrospun fibers; Poly(lactic acid) based nanocomposites; Bioglass nanoparticle; Zinc oxide nanoparticle; Functional scaffolds